MODIFIKASI SPECIAL TOOLS PEMASANG POWER OUTPUT SEAL BERSUDUT 90° PADA ENGINE ALLISON 250 – C20 SERIES DI SEKOLAH TINGGI PENERBANGAN INDONESIA - Ego Widoro; Diding Sunardi; Bagas Pradityo (Langit Biru: Jurnal Ilmiah Aviasi, 2017)
The schedule maintenance program of Allison 250-C20Series engine is required to keep the engine in airworthy condition. One of the schedule maintenance programs is planned to keep the engine oil flow system. This engine oil flow system can be disrupted if the seal on the power output seal which is keep the oil flow system were leak. The design of special tools modification power output seal installation aims to simplify the installation of power output seal when the engine power output still installed at the helicopter. It’s already made bysafety factor theory, Newton’s IInd law, Weight theory, and others theory which helping for making this modification tools. The purpose of modification is to attach power output seal in order to make it at the perpendicular. This is necessary to avoid tilt while installing seal. By modifying these special tools, there are a lot of free spaces made when installing the seal when the engine still installed at the helicopter, it became more flexible and lighter tools to use, if its compared with the prior modification of special tools. The parts of the special tools modification power output seal installation. The parts of special tools modification power output seal installation are power screw with allowable pressure is 3x10-6 kg/m2 , pusher seal cover with suitable area is 6,6x10-3 m 2 , pusher seal cover with suitable area is 6,4x10-3 m 2 and T-fasten screw with allowable shear stress is 4,15x10- 9 kg/m2 . This modification is capable to make the availability of long free space becomes wider 11 cm, and reduce the weight of the prior tools of up to 4x10-1 kg. The modification helped installation of power output seal esier when the engine is still installed on the Bell 206 helicopter